An empirical analysis of survey data about comprehension of collaboration - Ferguson, Ralph; C Idemudia , Efosa (Journal of Management and Science, 2020)
Statement of Problem: Collaboration a Means to Chaos Likert Type Survey Instrument: Collaborating with other students on academic assignments without having permission from your professor. A large Southwest university examines five years of data about the distinction that may contribute to ethical misconduct in the classroom and misguided actions as a future professional. The classroom models the evolution of technological shifts, which requires broader interaction across disciplines to manage projects. The encouragement to build teamwork skills through class assignments benefits preparation to enter the market economy to lead in e-commerce, social media, information Systems, and Business Analytics. The survey data indicates that collaboration with or without professorial approval is acceptable.